FORMULATION AND EVALUATION OF BILAYER SUSTAINED RELEASE TABLET OF ZOLPIDEM TARTRATE - Rabinarayan Parhi; Sanjay Kumar Bhupati; Padilam Suresh; Vijay Kumar (Indonesian Journal of Pharmacy, 2013)
The purpose of the present study was to develop a bilayer tablet of zolpidem tartrate (ZT) using sodium starch glycolate (SSG) as superdisintegrant in the immediate release (IR) layer and hydrophilic polymers such as hydroxypropyl methylcellulose (HPMC K4M), metalose 90 SH 4000, carbapol 974 PNF in sustained release (SR) layer. Both the IR and SR granules of ZT were evaluated for bulk density, tapped density, angle of repose, Carr’s index, Hausner ratio and loss on drying. All the values were found to be satisfactoy. The prepared bilayer tablets were evaluated for weight variation, hardness, friability, drug content, in vitro drug release, FT-IR studies, similarity factor and stability studies. In vitro dissolution studies were carried out in a USP dissolution apparatus I using 500mL of 0.01N HCl as dissolution medium. The formulations gave an initial burst effect to provide the loading dose of the drug followed by sustained release for 4 h. The data obtained were fitted to Zero order, First order, Higuchi’s model and Korsmeyer-Peppas equations. The release exponent (n) values for all the formulations were less than 0.45 indicating Fickian diffusion was the drug release mechanism. FT-IR studies indicated that there are no drug-excipient interactions. The similarity factor (f2) was calculated by comparing dissolution data of all the formulations with that of marketed bilayer tablet of ZT (Ambien CR). The f2 value was highest (70) for the formulation SF8 and was selected as promising formulation among all the developed formulations. The stability study was performed on the formulation SF8 at 25oC/60% RH, 30oC/75% RH and 40oC/75% RH (accelerated condition) for 3 months. The results indicated that there were no significant changes in aforesaid tablet properties.Key words: bilayer tablets, zolpidem tartrate, sustained release, higuchi’s equation, similarity factor